PENGARUH MOTIVASI TERHADAP KINERJA PEGAWAI PADA KANTOR CAMAT TUKKA KABUPATEN TAPANULI TENGAH - Pohan, Muhajrin (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
Based on the results of research on 29 respondents, shows the relationship of motivation to employee performance is high, where the calculation of product moment correlation is obtained 0.63. The results of the calculation of the coefficient of determination obtained 39.69% this picture shows that employee performance can be influenced by motivation by 39.69%. The remaining 60.31% is influenced by other factors not examined in this study. The simple linear regression equation obtained by Y = 17.87 + 0.48X shows a positive direction. Therefore t arithmetic 4.24> t table = 2.052, it can be concluded that Ho is rejected and Ha is accepted. Suggested In motivating employees, leaders must pay attention to factors that make employees motivated both the desires of the needs and expectations of each employee. With the fulfillment of employee desires, automatically the employees will try to show good performance.